2022
DOI: 10.4236/msce.2022.109001
|View full text |Cite
|
Sign up to set email alerts
|

Study of Magnetite Crystal Structure Extracted from Local Sands of Tegal Lenga Beach

Abstract: Magnetite (Fe 3 O 4 ) crystals have been synthesized from the natural iron sands of Tegal Lenga Beach with HCl (37%) as a solvent. Tegal Lenga Beach is a stretch of beach located in Kalisada Village, Seririt District, Buleleng Regency, Bali Province, Indonesia. Iron sand samples were obtained by extracting local natural sand from Tegal Lenga Beach by magnetic separation method. The iron sand sample was ground with agate mortar for 15 hours, then washed and rinsed with deionized water (DI water). Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Lastly, Almarasy et al [25] discussed the potential of hematite nanoparticles as flocculants in the treatment of raw water for drinking purposes. An earlier study into the crystal structure of sand from Tegal Lenga beach revealed the presence of magnetite microparticles [26]. Understanding the optical and magnetic properties of metal oxide materials, particularly hematite nanoparticles, is crucial for assessing their suitability for varied application fields.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, Almarasy et al [25] discussed the potential of hematite nanoparticles as flocculants in the treatment of raw water for drinking purposes. An earlier study into the crystal structure of sand from Tegal Lenga beach revealed the presence of magnetite microparticles [26]. Understanding the optical and magnetic properties of metal oxide materials, particularly hematite nanoparticles, is crucial for assessing their suitability for varied application fields.…”
Section: Introductionmentioning
confidence: 99%